URGENSI PENDIDIKAN KARAKTER GUNA CALON GENERASI EMAS BANGSA - Rifqi Taufiqul Hakim; Dinnie Anggraeni Dewi (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2022)
Character education aims to improve the quality of implementation and educational outcomes in schools that lead to the achievement of the character building and noble morals of students as a whole, integrated and balanced according to the competency standards of graduates. Through character education, students are expected to be able to independently improve and use their knowledge, study and internalize and personalize the values of character and noble morals so that they are manifested in daily behavior. In realizing character education, it cannot be done without the cultivation of values, because character comes from values about something. The individual character which is imbued with the principles of Pancasila, is grouped in two ways, namely the principle of four sports (heart exercise, thought, exercise, feeling and intention) and the values of obligation to God who is the creator, towards oneself, family, society, the nation and also the natural environment.